Espaços de Banach e operadores limitados - Barbosa, Mayssa da Silva (2017)
In this work, we study the Banach spaces, we show two important inequalities: Hölder and Minkwoski and finally we will demonstrate Baire’s Theorem to be used in the demonstration of the Banach-Steinhaus Theorem that assures us that continuous linear operators are limited.